SiMYB56 Confers Drought Stress Tolerance in Transgenic Rice by Regulating Lignin Biosynthesis and ABA Signaling Pathway - Xu, Weiya; Tang, Wensi; Wang, Chunxiao; Ge, Linhao; Sun, Jianchang; Qi, Xin; He, Zhang; Zhou, Yongbin; Chen, Jun; Xu, Zhaoshi; Ma, You-Zhi; Chen, Ming (Frontiers in Plant Science, 2020)
Foxtail millet (Setaria italica) originated in China and is generally cultivated in arid and barren soil. Through long-term harsh environmental selection, foxtail millet has acquired significant drought resistance. However, the molecular mechanism of foxtail millet drought resistance is still unknown. Here, we identified a drought-induced R2R3-MYB transcription factor SiMYB56 in foxtail millet. Overexpression of SiMYB56 significantly enhances tolerance to drought stress in transgenic rice plants at both the vegetative and the reproductive stage and has no adverse effect on its normal growth. Compared with wild-type controls, SiMYB56-overexpressing rice plants had lower MDA content and higher lignin content under drought conditions. Quantitative real-time PCR and Transcriptional activity assays demonstrated that SiMYB56 could activate expression of lignin biosynthesis genes under drought conditions. Also, we found that overexpression of SiMYB56 can led to ABA accumulation in the seeds transgenic rice plants. Further experiments showed that Overexpression of SiMYB56 can upregulate the expression of ABA synthesis and response related genes under drought conditions. In conclusion, SiMYB56 may enhance the drought resistance of transgenic rice plants by regulating lignin biosynthesis and ABA signaling pathway, making SiMYB56 a candidate gene for drought resistance improvement in gramineous crops.